Co-expression of IL-15/IL-15Ra complex enhances NKG2D-CAR T cell-mediated anti-pancreatic cancer immunity by activating the JAK/STAT5 signaling pathway - Chen, Yiran; Jin, Chenxu; Guo, Dandan; Hui, Xinhui; Ji, Yuzhou; Huang, Yunhe; Xue, Min; Gao, Yaoxin; Ren, Yaojun; Lin, Haizhen; Zhou, Ying; Jiang, Wenzheng (Frontiers in Immunology, 2025)
The application of CAR T therapy has significantly improved the efficacy of hematological tumors. However, there are still some challenges in the treatment of solid tumors, mainly because the complex immune microenvironment affects the proliferation of T cells, making T cells unable to function well. IL-15 has been reported to be a cytokine that can activate T cells and promote the proliferation and survival of T cells, especially CD8+ T cells. The complex formed by the high-affinity binding of IL-15 and IL-15Rα can bind to IL-2/IL-15Rβ/γ heterodimer on the surface of T cells, thereby activating downstream signaling pathways in T cells. In this study, we explored the activity of NKG2D-CAR T expressing IL-15/IL-15Rα complex (IL15C) on pancreatic cancer. The results of in vitro experiments showed that CAR T cells expressing IL15C had a stronger killing effect on tumor cells and showed a dose-dependent effect. In addition, the proliferation and anti-apoptosis levels of CAR T cells were enhanced after the co-expression of IL15C. IL15C regulates the function of T cells by activating the JAK/STAT5 signaling pathway of T cells. In vivo experiments showed that IL15C-NKG2D-CAR T cells could better inhibit tumor growth than the control group. This study provides a new idea for improving the efficacy of CAR T cells in the treatment of pancreatic cancer.